Modal analysis of car panels using finite element analysis - Hanouf, Zahir (Faculty of Engineering and Built Environment, Universiti Kebangsaan Malaysia, 2011)
This paper investigates the modal properties of car panels using finite element approach. The Finite Element models of the vehicle parts have been developed using the finite element of the fully car assembly model information and adapting it to our requirement. The modal analysis was performed to the natural frequencies and mode shapes. It is a requirement for any dynamical analysis or acoustical analysis that we should know the dynamic characteristics of the components. In this work, we clarified the methodology to carry out this characterization.